Evaluation and rationale of the performance of several elastomeric composites incorporating devulcanized EPDM. (April 2023) - Colom, X.; Carrillo-Navarrete, F.; Saeb, M.R.; Marin, M.; Formela, K.; Cañavate, J.
Abstract: Ethylene Propylene Diene rubber (EPDM), is present in many applications. However, its crosslinked structure makes difficult its recycling. The use of devulcanized EPDM, (dEPDM) as a component of elastomeric composites, is a real possibility to reuse EPDM scraps. In this study, three matrices (natural rubber (NR), styrene butadiene rubber (SBR) and EPDM rubber) have been tested including devulcanized EPDM as a recycled component. The EPDM previously was devulcanized using a thermomechanical process followed by microwave irradiation. The resulting devulcanized EPDM was blended with the matrixes and then the new compound was vulcanized again. The samples showed a general increase of their mechanical properties and their thermal stability specially marked for NR and SBR. Compositions including about 40 phr dEPDM within the EPDM matrix exhibited a difference in their general behavior that it was manifested by a general decrease in properties compared with lower amounts of dEPDM. In order to further understand this behavior, the samples were analyzed in terms of cross-link density, swelling degree, and scanning electron microscopy. The study of the microstructure of the samples indicated that microagglomerates of dEPDM are formed inside the samples. In case of NR or SBR the agglomerates were very linked to the matrix through the covalent bonds established in the crosslinking process. In the case of the EPDM matrix, the agglomerates presented less interfacial cross-links. The cross-linking takes place preferentially within the dEPDM microdomains and this results in a relative decrease in mechanical properties and thermal stability when compared to NR and SBR. Highlights: The focus is on whether dEPDM samples with NR, EPDM and SBR matrices have good properties and how much dEPDM can support. The three compounds tested showed a general increase of their mechanical and thermal properties for NR and SBR than EPDM. The microstructure indicate that agglomerates of EPDMd was formed inside the samples. The linkage is higher in NR than EPDM.